Classification of the acanthocephala - Amin, Omar M (Folia parasitologica, 2013)
In 1985, Amin presented a new system for the classification of the Acanthocephala in Crompton and Nickol's (1985) book 'Biology of the Acanthocephala' and recognized the concepts of Meyer (1931, 1932, 1933) and Van Cleave (1936, 1941, 1947, 1948, 1949, 1951, 1952). This system became the standard for the taxonomy of this group and remains so to date. Many changes have taken place and many new genera and species, as well as higher taxa, have been described since. An updated version of the 1985 scheme incorporating new concepts in molecular taxonomy, gene sequencing and phylogenetic studies is presented. The hierarchy has undergone a total face lift with Amin's (1987) addition of a new class, Polyacanthocephala (and a new order and family) to remove inconsistencies in the class Palaeacanthocephala. Amin and Ha (2008) added a third order (and a new family) to the Palaeacanthocephala, Heteramorphida, which combines features from the palaeacanthocephalan families Polymorphidae and Heteracanthocephalidae. Other families and subfamilies have been added but some have been eliminated, e.g. the three subfamilies of Arythmacanthidae: Arhythmacanthinae Yamaguti, 1935; Neoacanthocephaloidinae Golvan, 1960; and Paracanthocephaloidinae Golvan, 1969. Amin (1985) listed 22 families, 122 genera and 903 species (4, 4 and 14 families; 13, 28 and 81 genera; 167, 167 and 569 species in Archiacanthocephala, Eoacanthocephala and Palaeacanthocephala, respectively). The number of taxa listed in the present treatment is 26 families (18% increase), 157 genera (29%), and 1298 species (44%) (4, 4 and 16; 18, 29 and 106; 189, 255 and 845, in the same order), which also includes 1 family, 1 genus and 4 species in the class Polyacanthocephala Amin, 1987, and 3 genera and 5 species in the fossil family Zhijinitidae.
Keywords: Phylogeny; Animals; Acanthocephala; zvířata; fylogeneze